Stakeholder collaboration for organizing a yachting sport event - Abdullah, Nawal Hanim (Scholars' Press, 2014)
The Monsoon Cup event is an international yachting regatta held annually in Terengganu, Malaysia.Since its inception in the year 2005, many issues and critics have been reported in the local newspapers.The local residents have not been informed about the planning and infrastructure development for the purpose of organising the Monsoon Cup.The government did not ask for their opinion, views, comments and sharing of information with regards to the event.In Malaysia,input from the host community is often not seriously considered and seen to be practically irrelevant to the planning process (Din, 1997).Therefore, it is vital to investigate the views,engagement and forms of collaboration between the key stakeholders involved in the staging of a sailing event.The qualitative data collected from the stakeholders revealed that examining residents’ needs, knowledge and participation in a sporting event,and power distance issues were seen to be important factors in supporting the collaborative organisation of the Monsoon Cup event.This book provides useful information about the forms of collaborative organizing to industry players,policy makers,sport event organizer and public society.